1997
DOI: 10.1111/j.1432-1033.1997.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Lqh‐8/6, a Toxin‐Like Peptide from a Scorpion Venom

Abstract: Lqh-8/6 is a minor fraction isolated from the venom of the scorpion Leiurus quinquestriatus hebraeus. Here we describe the purification, amino acid sequencing and solution structure determination by NMR and molecular modeling of this peptide. Lqh-8/6 is a small polypeptide (38 residues) which contains 8 half-cystines and is highly similar to another venom component, chlorotoxin. Standard homonuclear methods were used to sequentially assign the proton NMR spectra and to collect spatial restraints for structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…The absence of exchange peaks between the two conformers indicates, however, a very slow exchange rate relative to the NMR time scales. For instance, such a feature was already observed for the Lqh-8/6, a toxin from a scorpion venom (64), or for a cyclic peptide (65). Several statistical studies (66,67) tentatively suggested possible correlations between the steric and electronic properties of the residues surrounding the proline and the stability of the cis isomer, by examination of peptide bonds from the Protein Data Bank (68).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of exchange peaks between the two conformers indicates, however, a very slow exchange rate relative to the NMR time scales. For instance, such a feature was already observed for the Lqh-8/6, a toxin from a scorpion venom (64), or for a cyclic peptide (65). Several statistical studies (66,67) tentatively suggested possible correlations between the steric and electronic properties of the residues surrounding the proline and the stability of the cis isomer, by examination of peptide bonds from the Protein Data Bank (68).…”
Section: Discussionmentioning
confidence: 99%
“…Exceptions have been found in a few cases, where conformational heterogeneity at proline residues could be identified by NMR spectroscopy. [9][10][11][12][13][14][15][16][17][18]20,22 The N2′ domain of the phage gene-3 protein accommodates in its folded form both the cis and the trans isomers of Pro161. In the crystal structures of the gene-3 protein, 23,24 this proline is cis in one molecule and not resolved in the other, and our kinetic analysis of the folding mechanism showed that, in fact, two folded forms, N trans (15%) and N cis (85%), coexist in solution.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] The biological importance of prolyl isomerization extends, however, beyond protein folding. Prolyl cis/trans isomerizations have been discovered in folded proteins [9][10][11][12][13][14][15][16][17][18][19] and assumed to be important for the function of such protein (e.g., in regulation). [20][21][22] Energy is required to change the cis/trans equilibrium at prolyl bonds, and this energy must be diverted from the Gibbs free energy of stabilization that becomes available in the course of conformational folding.…”
Section: Introductionmentioning
confidence: 99%
“…One solution to these problems is to employ the insecticidal viruses as the biological agents against specific pest insect hosts. So far many academic and industrial laboratories have input great resources in producing genetically modified or recombinant baculoviruses of accelerated toxic effects on target insects [32][33][34] . The specificity to target insects and the prominent bioactivity ARTICLES MOLECULAR VIROLOGY of the toxins rendered from the recombinant baculovirus make them useful in pest control [35][36][37] .…”
Section: Bioassays Of Recombinant Baculovirus Acmnpvbmk Itmentioning
confidence: 99%